In vitro degradation behaviour of hybrid electrospun scaffolds of polycaprolactone and strontium-containing hydroxyapatite microparticles - Melnik, Elizaveta; Weinhardt, Venera (Polymer degradation and stability, 2019)
We investigated the effect of varying content Sr-containing HA (SrHA) microparticles on the in vitro degradation of polycaprolactone (PCL) hybrid scaffolds. A degradation behaviour study was performed by immersing the scaffolds in phosphate buffered saline (PBS) solution at 37°C for 24 days. To evaluate the degradation rate, the following properties of the scaffolds were investigated: water uptake, pH buffer change and relative weight loss. The addition of SrHA microparticles significantly affected the PCL degradation process due to significant changes in the morphology of the hybrid scaffolds and improved wetting behaviour. The samples with a greater content of SrHA degraded faster in comparison with those with a lower content. The degradation rate of the scaffolds was revealed to increase as follows: PCL<PCL/SrHA 10 % wt<PCL/SrHA 15 % wt. Thus, the results demonstrated a higher degradation rate for the hybrid scaffolds, with a maximum weight loss of 2.41±0.10 % for a PCL/SrHA 15 % wt scaffold and a minimum weight loss of 0.90±0.05 % for pure PCL scaffolds implying an increased degradation rate for the hybrids. The hybrid PCL/SrHA scaffolds revealed increased wettability compared with pure PCL scaffolds that promoted the penetration of PBS into the scaffolds and increased their degradation rate in vitro.